PENGARUH STRATEGI INDEX CARD MATCH BERBANTUAN MEDIA KARTU BERGAMBAR TERHADAP HASIL BELAJAR SISWA KELAS V SDN PANDEAN LAMPER 05 SEMARANG - Tutut Triyani; Diana Endah Handayani; Singgih Adhi Prasetya (Jurnal Lensa Pendas, 2019)
This study motivated by the problems experienced by Pandean Lamper 05 Elementary School Semarang that classroom learning is still monotonous teacher-centered. The focus of the problem to be examined is is there an influence of the Index Card Match strategy assisted with pictorial card media on the learning outcomes of fifth grade students of Pandean Lamper 05 SDN Semarang. This study uses a quantitative approach in the form of a quasi pre-experimental design withtypes one-group pretest-posttest. The population in this study were all VA students of Pandean Lamper 05 Elementary School Semarang. The sample taken consisted of VA classes totaling 38 students using saturated sampling techniques. Data collection methods used were interviews, documentation, test methods (pretest-posttest), and observation sheets. The instrument in this study is a test in the form of multiple choice questions that have been tested for validity, reliability, degree of difficulty, and differentiation. The results of this study can be concluded that thestrategy is Index Card Match assisted bycard media pictorialtowards the learning outcomes of class V students of Pandean Lamper 05 Elementary School Semarang